Polyunsaturated fatty acid metabolism in Atlantic salmon (Salmo salar) undergoing parr-smolt transformation and the effects of dietary linseed and rapeseed oils - Tocher, Douglas R; Bell, J Gordon; Dick, James R; Henderson, R James; McGhee, Fiona; Michell, D; Morris, Paul C (Springer, 2000)
Duplicate groups of Atlantic salmon parr were fed diets containing either fish oil (FO), rapeseed oil (RO), linseed oil (LO) or linseed oil supplemented with arachidonic acid (20:4n-6; AA) (LOA) from October (week 0) to seawater transfer in March (week 19). From March to July (weeks 20-34) all fish were fed a fish oil-containing diet. Fatty acyl desaturation and elongation activity in isolated hepatocytes incubated with [1-14C]18:3n-3 increased in all dietary groups, peaking in early March about one month prior to seawater transfer. Desaturation activities at their peak were significantly greater in fish fed the vegetable oils, particularly RO, compared to fish fed FO. Docosahexaenoic acid (22:6n-3:DHA) and AA in liver and gill polar lipids (PL) increased in all dietary groups during the freshwater phase whereas eicosapentaenoic acid (20:5n-3;EPA) increased greatly in all groups after seawater transfer. The AA/EPA ratio in tissue PL increased up to seawater transfer and then decreased after transfer. AA levels and the AA/EPA ratio in gill PL were generally higher in the LOA group. The levels of 18:3n-3 in muscle total lipid were increased significantly in the LO, LOA and, to a lesser extent, RO groups prior to transfer but were reduced to initial levels by the termination of the experiment (week 34). In contrast, 18:2n-6 in muscle total lipid was significantly increased after 18 weeks in fish fed the diets supplemented with RO and LO, and was significantly greater in the FO and RO groups at the termination of the experiment. Gill PGF production showed a large peak about two months after transfer to seawater. The production of total PGF post-transfer was significantly lower in fish previously fed the LOA diet. However, plasma chloride concentrations in fish subjected to a seawater challenge at 18 weeks were all lower in fish fed the diets with vegetable oils. This effect was significant in the case of fish receiving the diet with LOA, compared to those fed the diet containing FO. The present study showed that ...